A conceptual framework for the analysis of civil-military relations and intelligence. Issue 4 (2nd October 2018) - Bruneau, Thomas C.
ABSTRACT: The article argues that current conceptual approaches in civil-military relations are deeply flawed resulting in its irrelevance in analyzing major issues including war and the collapse of democracy. After highlighting major flaws in the work of the late Samuel Huntington and those who follow his approach, the article argues that other conceptual approaches, including Security Sector Reform, are also flawed, or in the case of the "military effectiveness" literature, largely irrelevant. In explaining the main causes of the flawed conceptual literature, the article highlights the absence of good data and challenges in methodology. While arguing that military forces are very unlikely to engage in armed combat, it highlights the roles and missions which in the world today are implanted by these forces. As it is virtually impossible to prove effectiveness of the armed forces in these roles and missions, the article proposes a conceptual approach based on requirements.